Cytotoxic effect of polyisoprenoids from Rhizophora mucronata and Ceriops tagal leaves against widr colon cancer cell lines - Dini Permata Sari,; Mohammad Basyuni,; Hasibuan, Poppy Anjelisa Zaitun; Ridha Wati,; Sumardi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The mangrove plant is known to produce secondary metabolite compounds, mainly isoprenoids. Polyisoprenoids (dolichol and polyprenol) are known to have antimicrobial, anticancer and antiviral activity. Therefore, this study aimed to determine the cytotoxic effects of polyisoprenoids from Rhizophora mucronata and Ceriops tagal leaves by evaluating the induction of apoptosis and cell cycle arrest and the inhibition of the expression of Bcl-2 and cyclin D1 in WiDr colon cancer cells. Cell death was determined based on IC50 values in MTT assays. The induction of apoptosis and alterations in the cell cycle were observed by flow cytometry. The expression of Bcl-2 and cyclin D1 proteins, which play a role in apoptosis and cell cycle regulation, was observed by immunocytochemistry. The results showed that polyisoprenoids from R. mucronata and C. tagal leaves exhibited toxicity against the WiDr cell line, with IC50 values of 278 ± 5.77 and 276 ± 9.54 μg/mL, respectively. Polyisoprenoids from R. mucronata and C. tagal leaves significantly induced apoptosis and caused cell cycle arrest in G0/G1 phase, while also decreasing the expression of Bcl-2 and cyclin D1. Our results confirmed that polyisoprenoids from R. mucronata and C. tagal leaves have the potential to be developed as anticancer agents for colon cancer.